Denmark : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper analyzes investment slowdown in Denmark. The post-global financial crisis (GFC) weakness in Denmark's aggregate investment cannot be fully explained by the output slowdown. The baseline accelerator model confirms that output slowdown played a role, but post-GFC investment has fallen beyond the level explained by output movements in most of the post-GFC period. Most recently, investment converged to the level explained by output movements. The augmented accelerator model suggests that additional factors, such as high leverage, weak competition, and elevated policy uncertainty, also had a significant impact. Panel regressions using a panel of advanced economies show that reduction in leverage and product market reforms can boost investment in the medium term. Well-designed policies are needed to boost private investment.